Сardioprotective agents with biaromatic structure. Part 3. Sodium channel blockers - G. V. Mokrov (LLC "Publisher OKI", 2022)
This review continues a series of reviews on the analysis of compounds with cardioprotective properties in a number of biaromatic structures, which include a range of sodium channel blockers. Among voltage-gated sodium channels, the Nav1.5 isoform is the most abundant in the heart. Sodium channel blockers have historically been called "class I antiarrhythmics". Among the compounds of this type, a biaromatic structure mainly have the Nav1.5 late current blockers belonging to the Id subclass of antiarrhythmic drugs. Leader molecules from this subgroup, such as ranolazine, GS-458967, and F15845, reduce action potential recovery time and suppress trigger activity induced by early post-depolarization. They are effective for the treatment of stable angina and ventricular tachycardia.